Geomagica research paper - Bayquen, Katherine G. (1995)
GeoMAGICA is a software package which includes GeoMAGICA, the actual program GeoEDIT, the customized database editor of the software, and 'Nasaan sa 'Pinas si Annie Batumbakal', the educational game which tests the users of their knowledge on Philippine geography and history. GeoMAGICA package is a multimedia which runs under the Windows platform, and is also made accessible through the Internet. Being so, it can showcase the wonders of the Philippines through a wider audience and thus can be an advantage for the promotion of the Philippines tourism. It can likewise be used by students as an effective supplementary material because of its interactive nature.